2020
DOI: 10.1093/ibd/izaa015
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress in Subepithelial Myofibroblasts Increases the TGF-β1 Activity That Regulates Fibrosis in Crohn’s Disease

Abstract: Background Endoplasmic reticulum (ER) stress is an essential response of epithelial and immune cells to inflammation in Crohn’s disease. The presence and mechanisms that might regulate the ER stress response in subepithelial myofibroblasts (SEMFs) and its role in the development of fibrosis in patients with Crohn’s disease have not been examined. Methods Subepithelial myofibroblasts were isolated from the affected ileum and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…It has recently been shown that endoplasmic reticulum (ER) stress, which occurs following the accumulation of misfolded proteins, induces TGF-β1 gene expression. 73 4.11.3 | Pro-inflammatory cytokines favour matrix remodelling and decrease wound healing Stricture myofibroblasts exposed experimentally to the proinflammatory cytokines IL17A and TNF release MMP-3 and MMP-12, in addition to increasing TIMP-1 and collagen production. 42 Moreover, IL-17E increased MMP-3 and MMP-12 without concomitant stimulation of TIMP and collagen.…”
Section: Tgf-β Tips the Balance Towards Fibrosismentioning
confidence: 99%
“…It has recently been shown that endoplasmic reticulum (ER) stress, which occurs following the accumulation of misfolded proteins, induces TGF-β1 gene expression. 73 4.11.3 | Pro-inflammatory cytokines favour matrix remodelling and decrease wound healing Stricture myofibroblasts exposed experimentally to the proinflammatory cytokines IL17A and TNF release MMP-3 and MMP-12, in addition to increasing TIMP-1 and collagen production. 42 Moreover, IL-17E increased MMP-3 and MMP-12 without concomitant stimulation of TIMP and collagen.…”
Section: Tgf-β Tips the Balance Towards Fibrosismentioning
confidence: 99%
“…Moreover, our recent study showed that the UPR and its downstream signaling pathways can be manipulated through epigenetic regulations. We showed that expression of ER stress sensors increased significantly in subepithelial myofibroblasts of strictured intestine from patients with fibrostenotic Crohn's disease [9]. Increase in ER stress response featured with overexpression of GRP78, XBP1s, and ATF6α can be also reproduced in the normal intestinal subepithelial myofibroblasts when treated with tunicamycin, which is an ER stress agonist [9].…”
Section: Epigenetic Regulation Of the Uprmentioning
confidence: 86%
“…These stresses commonly include changes in calcium homeostasis, viral or bacterial infection, inflammation, nutrition or energy deficiency, hypoxia, lipid overload, altered redox status, as well as oncogene activation in cancer [7,10]. During UPR, transcription factors such as ATF6, XBP-1 are activated and translocated to the nucleus to initiate transcription of genes involved in inflammation, cell proliferation and fibrosis [9,11]. In addition, ER stress plays a role in cellular differentiation, antigen presentation, and stem cell renewal capacity [8].…”
Section: The Cause Of Uprmentioning
confidence: 99%
See 2 more Smart Citations